Under Penalty of Death: - Dinaldo Filho (Revista Brasileira de Estudos da Presença)
The text analyzes the figural aspects of The Thin Blue Line (Morris, 1988) and A Short Film About Killing (Kieślowski, 1988) as reveries of justice driven by the abolitionist imagination of the death penalty. This imagination finds its power in the inviolability of human life as a sense of justice experienced through poetic treatments of the death penalty as a visual motif. The films are approached via a theoretical dialogue between Bachelard’s concept of poetic reverie and Dubois’ Figural question, as they allow us to investigate fiction and documentary as filmic reveries that lead us to a poetic and political experience with the phenomenological world of justice.